Bibliometric Analysis of The Concept of "Organizational Differences" Using Visual Mapping Technique - DEVECİYAN, MERİ TAKSİ (ADAMOR, Toplum Araştırmaları Merkezi, 2024)
In this study, it is aimed to perform a bibliometric analysis of the research related to the concept of organizational differences and to make inferences about the general structure of the field. In this direction, in the research, 303 scientific publications on "organizational differences" were examined with the bibliometric analysis method using the Web of Science database, and then the obtained data were visualized using the VOSviewer software program. Bibliometric methods such as keyword analysis, citation analysis, co-author analysis, co-citation analysis of authors were used on the identified scientific publications. Using bibliometric methods, a comprehensive view of the dynamics of the field is presented; the development of the literature on the concept of "organizational differences" has been mapped by determining the basic studies, types, years, authors, countries and publication areas. As a result of the study, it was found that the subject of "organizational differences" was not studied sufficiently in the literature; the most publications on a country basis were from America, the most publications on a year basis were published in 2019, and the most commonly cited author was Alstemark B. It is thought that the findings obtained as a result of the analysis will provide resources for future studies on "organizational differences".
"Örgütsel Farklılıklar" Kavramının Görsel Haritalama Tekniği Kullanılarak Bibliyometrik Analizi
Keywords: Organizational Differences; Bibliometric Analysis; Vosviewer